2014
DOI: 10.1589/jpts.26.1433
|View full text |Cite
|
Sign up to set email alerts
|

Upper Extremity Problems in Doner Kebab Masters

Abstract: [Purpose] Doner kebab is a food specific to Turkey; it is a cone-shaped meat placed vertically on a high stand. The doner kebab chefs stand against the meat and cut it by using both of their upper extremities. This work style may lead to recurrent trauma and correspondingly the upper extremity problems. The aim of this study was to investigate the upper extremity disorders of doner chefs. [Subjects and Methods] Doner kebab chefs were selected as the study group, and volunteers who were not doner kebab chefs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
3
8
0
Order By: Relevance
“…diagnoses) at the elbow, forearm and/or wrist were found in 56% (39/70), of which 12/20 (70%) grinders, 14/24 (54%) packers and 13/26 (42%) control persons. These results are consistent with previous studies showing a prevalence rate of symptoms between 21% and 71% in the study group and between 6% and 50% in the control group [34][35][36][37][38][39][40][41][42][43][44][45][46]. With regard to diagnoses, existing studies report a prevalence between 21% and 56% in the study group compared to 5-22% in the control group [35,36,38,39,40,42].…”
Section: Discussionsupporting
confidence: 92%
“…diagnoses) at the elbow, forearm and/or wrist were found in 56% (39/70), of which 12/20 (70%) grinders, 14/24 (54%) packers and 13/26 (42%) control persons. These results are consistent with previous studies showing a prevalence rate of symptoms between 21% and 71% in the study group and between 6% and 50% in the control group [34][35][36][37][38][39][40][41][42][43][44][45][46]. With regard to diagnoses, existing studies report a prevalence between 21% and 56% in the study group compared to 5-22% in the control group [35,36,38,39,40,42].…”
Section: Discussionsupporting
confidence: 92%
“…The design of our cross-sectional study with a control group, physical examination of the subjects, and the use of a questionnaire can be found in several studies related to different industries. Our literature research showed a prevalence of upper extremity pain (i.e., symptoms) of between 21% and 71% in the study group and between 6% and 50% in the control group [56][57][58][59][60][61][62][63][64][65][66][67][68]. This is in line with our investigation where symptoms were reported in the first questionnaire by 8/20 (40%) grinders, 14/24 (58%) packers, and 11/26 (42%) people in the control group.…”
Section: Prevalence Of Symptoms and Diagnosessupporting
confidence: 90%
“…However, since WMSDs represent a complex condition that can be influenced by individual, environmental, psychosocial, and organizational factors, this simplified interpretation is only one possible aspect in a multi-level approach with numerous interactions and thus might explain some contradictory results [77,78]. Variations in the duration of exposure, work interruptions through less monotonous and stressful pre-processing and post-processing activities, psychosocial factors, the level of training, and income disparities may have such an influence that the primary work tasks lose relevance with regard to upper extremity WMSDs [65,66].…”
Section: Interpretation Of the Resultsmentioning
confidence: 99%
“…His work involved placing it in a cooker and then cutting and serving it in desired portions. Since slicing the doner with a long, heavy knife involves repeated arm movement, men in this occupation often develop upper extremity problems such as lateral/medial epicondylitis and tendinitis 10 ) . Our patient had previously been diagnosedas having a biceps tendon rupture.…”
Section: Introductionmentioning
confidence: 99%